Additive predictive value of low testosterone level in hypertensive men with hypercholesterolemia. (3rd October 2022) - Ioakeimidis, N; Terentes-Printzios, D; Antonopoulos, A; Dima, I; Gourgouli, I; Solomou, E; Aznaouridis, C; Chatzistamatiou, E; Lazaros, G; Kalfountzos, D; Tsioufis, C; Vlachopoulos, C
Abstract: Purpose: Hypercholesterolemia is common in hypertensive patients and its presence increases the risk of cardiovascular (CV) complications. Decreased concentration of testosterone appears commonly in men with hypertension, and is an independent predictor of CV events. We investigated the utility of testosterone concentration measurement as an aid in the risk prediction of CV events in men with arterial hypertension and high LDL levels. Methods: A cohort of 321 men with arterial hypertension and without known diabetes or atherosclerotic CVD (mean age: 54±9 years) were followed for the occurrence of major adverse cardiovascular events (MACE), (CV death, coronary artery disease, stroke). Total testosterone (TT) and LDL levels were measured in all patients. We used Cox proportional hazards regression to analyze the associations between LDL, serum testosterone and CV outcomes. Results: During a mean follow-up of 6 years (range: 1–11 years), 31 (9.5%) patients demonstrated a MACE. Patients in the CV-event group were older and they had higher LDL and lower baseline TT levels compared to subjects in the event-free survival group (all P<0.01) while BMI, systolic blood pressure and smoking exposure (pack-years) were similar. Based on the observed distribution of baseline LDL levels the study cohort was divided in two groups: low LDL (<130 mg/dl) and high LDL (≥130 mg/dl). According to baseline TT level distribution the study cohort was divided in two groups: normal TT (>4.0 ng/mL) and low TT (≤4.0 ng/mL). Subjects in the high LDL group, had no increased risk of MACE compared to subjects in the low LDL group (HR 1.35; 95% CI 0.75–2.04) in the multivariable model. Moreover, there was no statistically significant association between low TT and risk of MACE. HR for low TT vs high TT was 1.48 (95% CI 0.85–2.16). We then subdivided the two LDL (high vs low) groups into subgroups according to presence of low or normal TT. Cox regression analysis revealed that the subgroup of men with both low TT and high LDL had an almost 2-fold higher risk of MACEs compared to the other three LDL/TT subgroups (adjusted hazard ratio: 2.07; 95% CI 0.94–3.56, P=0.035). Figure 1 shows the cardiac event-free survival curve of males with both baseline low TT and high LDL level with that of males in the other three LDL/TT subgroups (log rank: 11.3, P=0.008). Conclusion: Low testosterone concentration is associated with a shorter event-free period in hypertensive patients with higher LDL levels. The measurement of testosterone concentration may be useful to further stratify the risk of middle-aged men with arterial hypertension and hypercholesterolemia. Funding Acknowledgement: Type of funding sources: None.